THE (UN)SEIZABILITY OF FAMILY ASSETS: HYPOTHESES AND EXCEPTIONS (REMUNOM, 2024)
This scientific article examines, based on specific legislation, the hypotheses and exceptions to the unseizability of family assets. The study begins with a comprehensive analysis of the concept of family property, its historical origin in Brazil and the distinction between legal and voluntary family property. It also explores the legal nature of family property and the way in which this institute relates to the right to housing, the theory of minimum assets and the principle of human dignity, all of these teachings to guarantee the basis for the main theme of this work, the possibilities and impossibilities of seizing family property. The methodology adopted to carry out the study was exploratory, in which it was used as references, the analysis of the Constitution of the Federative Republic of Brazil of 1988, Law n° 8.009/90, the Civil Code of 2002, CPC/2015, summaries, jurisprudence, academic articles and content websites was used as a reference. legal. The article concludes by highlighting the relevance of this topic, its legal and social implications, and points to the importance of a skillful judgment by the magistrate, aiming to ensure, in the most effective way possible, that creditors and debtors have their rights and particularities taken into consideration. in the search for a fair decision.